Analisis Pengaruh Volume Perdagangan Saham dan Return Pasar terhadap Reaksi Pasar pada Saham Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia - Ni Luh Tania Ningsih; Ni Luh Putu Anom Pancawati; Armi Sulthon Fauzi (CV Global Research Publication, 2026)
This study aims to analyze the effect of Stock Trading Volume and Market Return on Market Reaction in banking sector stocks listed on the Indonesia Stock Exchange. The research employs a quantitative method using secondary data from 2021 - 2025. The analysis techniques include the t-test for individual effects and the F-test for simultaneous effects. The results indicate that Stock Trading Volume does not significantly affect Market Reaction, whereas Market Return has a significant effect on Market Reaction. Simultaneously, Stock Trading Volume and Market Return significantly influence Market Reaction, suggesting that the combination of quantitative and fundamental information provides a stronger signal for investors. These findings are consistent with the Efficient Market Hypothesis, Signaling Theory, and Market Reaction Theory, which assert that investment decisions are influenced by relevant information and adequate market signals. This study recommends that investors focus more on Market Return when making investment decisions, that banking companies improve transparency and quality of information, and that future researchers consider additional variables and more complex analytical methods to better understand market dynamics.